A systematic review of parasitic diseases of otters - Cotey, Stacy R.; Reichard, Mason V. (Frontiers in Mammal Science, 2025)
Due to their semi-aquatic lifestyles, otters are exposed to pathogens from both terrestrial and aquatic systems. Although parasites are a natural part of any system, they are a source of environmental stress for Lutrinae of which twelve of the fourteen species are currently listed as threatened or endangered. Climate change, fragmentation, habitat loss, and increasing interactions with humans are directly affecting otter populations and increasing the risk of exposure to diseases. Identifying parasitic diseases and the potential threat to otters is the first step in minimizing this stressor. In this paper, we systematically reviewed the literature and summarized parasitic diseases reported for Lutrinae. We analyzed the overall prevalence of the parasites reported and noted major emerging parasites of concern for otter species. Overall, there were 146 genera representing 164 parasite species listed for 10 otter species. No parasite studies were found for Smooth-coated Otters (Lutrogale perspicillata), Hairy-nosed Otters (Lutra sumatrana), and Congo Clawless Otters (Aonyx congicus). Published studies were also limited for 7 additional otter species indicating a need for surveys of parasites in otters.